The Effect of Alert Education (Respiratory Emergency Alert) on Increasing Parents' Knowledge about the Handling of ISPA in Children at the Telaga Biru Health Center - Silvani Mohamad Ibrahim; Zainuddin; Rini Wahyuni Mohamad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Acute Respiratory Tract Infection (ARI) is one of the leading causes of morbidity and mortality in children. The high incidence of ISPA in the Telaga Biru Health Center work area shows the need for efforts to increase parental knowledge in carrying out appropriate initial handling. SIGAP Education (Respiratory Emergency Alert) is one of the health education innovations designed to improve parental preparedness in dealing with respiratory disorders in children. Objective: This study aims to determine the effect of SIGAP (Respiratory Emergency Alert) education on increasing parents' knowledge about the handling of ISPA in children at the Telaga Biru Health Center. Methods: This study used a quantitative method with a pre-experimental design of one group pretest-posttest. The research was carried out at the Telaga Biru Health Center in January-February 2026. The research sample amounted to 44 parents who had children with ARI. Data were collected using a knowledge questionnaire and analyzed using a paired t-test. Results: The results showed that before being given SIGAP education, most of the respondents had a moderate level of knowledge of 21 people (47.7%), 20 people (45.5%) of high knowledge, and 3 people of low knowledge (6.8%). After being given SIGAP education, the majority of respondents had a high level of knowledge of 41 people (93.2%) and a medium level of knowledge of 3 people (6.8%). The results of the paired t-test showed an increase in the average knowledge value from 2.39 ± 0.618 to 2.93 ± 0.255 with a p value of < 0.001, which shows a significant influence of SIGAP education on increasing parental knowledge about the treatment of ISPA in children. Conclusion: SIGAP (Respiratory Emergency Alert) education has proven to be effective in increasing parents' knowledge about the handling of ISPA in children at the Telaga Biru Health Center. This educational program can be used as one of the health promotion strategies to increase family preparedness in dealing with respiratory disorders in children.